Education And Gender Equality: A Case Study Of Muslim Female Students In Malaysia - Moses Schleimer, Simon (2016)
Both the internationalized and globalized processes of the country and the traditional norms and conservative religious concepts regarding gender roles, work and family influence the lives of women in Malaysia. The latter can hinder them to tap their full potential: Despite outnumbering male students in secondary school and university, only 53 percent of women between the age of 15 and 64 are employed in Malaysia (Economic Planning Unit Malaysia, 2015, p. 3-7). Against this background, the question arises how educationally successful Muslim female students develop individual educational processes to lay the foundation to pursue successful careers afterwards. The study refers to fifteen narrative in-depth interviews with Muslim female students about chances and challenges within their education. The interviews were analysed through the hermeneutic cultural analysis methodology “scenic understanding” according to Lorenzer (2006 [1985]). It is outlined that leadership programs in school can help the female students to develop skills to pursue a successful education and career. Consequently, leadership programs contribute to the sustainable development of gender’s equality and women’s empowerment.